Multi-centre prospective internal and external evaluation of the Brompton Harefield Infection Score (BHIS). Issue 2 (March 2018) - Rochon, Melissa; Jarman, Julian WE; Gabriel, Joseph; Butcher, Lisa; Morais, Carlos; Still, Martin; Ahmed, Ishtiaq; Petrou, Mario; Trimlett, Richard; DeSouza, Anthony; Yadav, Rashmi; Raja, Shahzad G
Background: Previously, we reported that the Brompton Harefield Infection Score (BHIS) accurately predicts surgical site infection (SSI) after coronary artery bypass grafting (CABG). The BHIS was developed using two-centre data and stratifies SSI risk into three groups based on female gender, diabetes or HbA1c > 7.5%, body mass index ≥ 35, left ventricular ejection fraction < 45% and emergency surgery. The purpose of this study was to prospectively evaluate BHIS internally as well as externally. Methods: Multi-centre prospective evaluation involving three tertiary centres took place between October 2012 and November 2015. SSI was classified using the Public Health England protocol. Receiver operating characteristic (ROC) curves assessed predictive accuracy. Results: Across the four hospital sites, 168 of 4308 (3.9%) CABG patients had a SSI. Categorising the hospitals by BHIS score revealed that 65% of all patients were low risk (BHIS 0–1), 26% were medium risk (BHIS 2–3) and 8% were high risk (BHIS ≥ 4). The area under the ROC curve was in the range of 0.702–0.785. Overall area under the ROC curve was 0.709. Conclusions: BHIS provides a novel, internally and externally evaluated score for a patient's risk of SSI after CABG. It enables clinicians to focus on strategies to prospectively identify high-risk patients and improve outcomes.